System process documentation of processing of moringa leaves into moringa powder - Medina Melissa R. (BIO Web of Conferences)
Moringa oleifera, commonly known as malunggay, has a high nutritional and medicinal value. With these, the global market for moringa ingredients is increasing because of the change to a more essential or healthy lifestyle. The moringa leaves are highly perishable to maintain their quality. This study shows several processing techniques for dried moringa leaves. Furthermore, the study examined the material balance of 25kg of freshly harvested moringa leaves. The weight increased by 4% in the initial washing and 29% in the secondary washing due to the leaves’ water absorption capacity. Spin dryer removal was 42%, while mechanical dryer removal was 23%. The study achieved 10% material recovery from harvest to packaging. As a result of the study, one of the major issues for moringa processing is its high investment costs, with a total equipment cost of Php 1,398,355.00, and its labor intensiveness, particularly in the destemming procedure (5 kg per hour). The lack of moringa plantations is one of the constraints for establishing the processing, as this will hamper the operation. As a recommendation, increasing moringa leaves for a stable supply of raw materials or establishing a small-scale processing facility for lower investment costs.